Respuestas

2012-04-28T21:10:12+02:00

son: (a+b).(a-b)= a^2-b^2

 

         (a+b)`2= a^2+2.a.b+b^2

 

         (a+b)^3=a^3+3.a^2.b+3.a.b^2+b^3      

 

 

 

 

 

 

 

 

 

2012-04-28T21:11:32+02:00

Las más importantes y de gran utilidad son:

 

\begin{gathered} a^2 - b^2 = \left( {a + b} \right)\left( {a - b} \right) \hfill \\ a^2 \pm 2ab + b^2 = \left( {a \pm b} \right)^2 \hfill \\ a^3 \pm b^3 = \left( {a \pm b} \right)\left( {a^2 \mp ab + b^2 } \right) \hfill \\ a^3 \pm 3a^2 b + 3b^2 a \pm b^3 = \left( {a \pm b} \right)^3 \hfill \\ \end{gathered}